Information Services with a Muhasabah Approach to Increasing the Career Maturity of Adolescent - Malim Soleh Rambe; Khairul Amri; Eli Marlina Harahap; Rajab Ansari (CV. Creative Tugu Pena, 2024)
Adolescent career maturity has an important role in achieving their goals. Teenagers who have a good career understanding can help determine their career choices. Career understanding is obtained by understanding themselves and looking for various information that is used to support career alternatives. This research was conducted at Kartika Padang High School. This research aims to increase the career maturity of teenagers using information services with a muhasabah approach. The research method used was an experiment in the form of a one group pre-test post-test design. The population was 355 people and the sample was 33 people. The instrument for this research is the Adolescent Career Maturity Scale which is proposed using a Likert scale measurement. The data is analyzed using descriptive statistics with the help of SPSS version 25.00. The research results showed that the career maturity of teenagers before being given treatment was in the low category, while after being given treatment was in the high category. There was an increase in teenagers' career maturity before and after being treated with information services using a muhasabah approach. Thus, information services with a muhasabah approach can facilitate optimal youth development to increase youth career maturity. This is evidenced by the increasing planning, exploration and realization of teenagers' career decisions in the future.